Plague Time: Space, Fear, and Emergency Statecraft in Early Modern Italy - Eckstein, Nicholas A. (Renaissance and Reformation / Renaissance et Réforme, 2021)
Michel Foucault argued famously that early modern European governors responded to plague by quarantining entire urban populations and placing citizens under minute surveillance. For Foucault, such sixteenth- and seventeenth-century policies were the first steps towards an authoritarian paradigm that would only emerge in full in the eighteenth century. The present article argues that Foucault’s model is too abstracted to function as a tool for the historical examination of specific emergencies, and it proposes an alternative analytical framework. Addressing itself to actual events in early modern Italy, the article reveals that when plague threatened, Florentine and Bolognese health officials projected themselves into a spatio-temporal dimension in which official actions and perceptions were determined solely by the spread of contagion. This dimension, “plague time,” was not a stage on the irresistible journey towards Foucault’s “utopia of the perfectly governed city.” A contingent response to a recurrent existential menace, plague time rose and fell in response to events, and may be understood as a season.